Persepsi Masyarakat Desa Jake Kelurahan Simpang Tiga Kuantan Singingi Terhadap Penggunaan Kain Pembungkus Furoshiki Sebagai Budaya Baru Melalui Pelatihan PkM - Nasution, Yenny Aristia; Widiati, Sri Wahyu; Nimashita, Hana; Yohani, Adisthi Martha; Rahayuningtyas, Putri (Unri Conference Series: Community Engagement, 2024)
The activity of introducing furoshiki culture to the community is one of the efforts to preserve the environment. Furoshiki with high aesthetic value is expected to attract the attention of the community to use it as a substitute for plastic packaging. Through the Community Service (PkM) activity organized by the Japanese Language Education Study Program, FKIP, Riau University, an introduction to the history and culture of furoshiki, the practice of using furoshiki, and distributing questionnaires was carried out to determine the community's perception of the potential for accepting furoshiki as a new culture and habit in the local community. The target community was 50 members of the PKK of Jake Village, Simpang Tiga Village, Kuantan Tengah District, Kuantan Singingi Regency, Riau Province. From the results of the questionnaire, 100% of participants agreed to practice the use of furoshiki, 98% of participants agreed to accept furoshiki as a new culture, 100% of participants agreed with the efforts and means of spreading furoshiki and 90% of participants were interested in furoshiki. Based on these results, it can be said that the community can accept furoshiki culture well to become part of everyday life. However, in order to achieve optimal sustainability, efforts are needed to introduce furoshiki culture more widely in society and to consistently get used to using furoshiki.